Trestné činy z nenávisti v európskej perspektíve - Jozef Záhora (Acta Universitatis Carolinae. Iuridica)
Hate crimes are considered a serious type of crime because hatred as such, can destroy civil society. They have an impact not only on individual victims and their communities but also on society. The author in brief presents the concept of hate crimes and its basic characteristics and connection to other crimes. The most important actors creating policies to combat hate crimes and hate speech in Europe are the Council of Europe, the European Union, and the Organization for Security and Co-operation in Europe. For this reason, the author presents current and upcoming legal instruments specifically designed for the fight against hate crimes in Europe. As part of the discussion, he points out possible difficulties related to the creation of a unified framework for combating hate crimes in Europe and reflects on the possibilities of implementing these instruments into national law.